Review of Scydmaenus species of continental China described by Herbert Franz (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
Most species of Scydmaenus Latreille described by Herbert Franz are impossible to identify without re-examination of the type material. The Chinese fauna is no exception and it is easy to find specimens whose aedeagi resemble those illustrated by Franz, but the only way to identify them is to directly compare new material with types. On the other hand, the aedeagi of type specimens often look slightly or even strongly different from those illustrated in original descriptions, which increases the confusion. Six species of Scydmaenus described by Franz and occurring in continental China are here redescribed, and the aedeagi of holotypes are illustrated in detail: S. chinensis, S. fukiensis, S. kunmingensis, S. sinensis, S. szechuanensis, and S. kiautunensis. The first five species are confirmed to belong in the nominotypical subgenus; S. kiautunensis is transferred from Scydmaenus (s. str.) to the subgenus Nepaloscydmaenus Franz. As previous checklists of Palaearctic or Eastern Asian Scydmaeninae contain incomplete data, an updated and annotated checklist of Scydmaenus species so far recorded from the People’s Republic of China, Taiwan and Hong Kong is given, with comments on possible misidentifications, possible synonymies and distributional issues.